The mirror test : America at war in Iraq and Afghanistan - Weston, J. Kael (New York : Alfred A. Knopf, 2016)
A former State Department official draws on a wide range of voices and stories to explore the human costs of conflict, asking hard questions about the U.S. wars in Iraq and Afghanistan.
Prologue: Twentynine Palms, California -- Part I. The wrong war -- Quagmire -- Friends and enemies -- Phantom fury or new dawn? -- Happy birthday -- The potato factory -- Clear, hold, build -- Helo down -- Collaboration -- KIA in Mayberry -- When senators and generals talk -- Sara al Jumaili and the last grand mufti -- A farewell to Fallujah -- The 93 -- To Monument Valley -- Part II. The right war -- Deeper into the Muslim world -- Dilawar of Yakubi -- Khost U -- A handshake, or two -- Reformed Taliban -- The ego has landed -- Life after Guantanamo -- The dead of Sabari District -- The commander and the top student -- Jackpots and dryholes -- Motor City -- Escalation -- Our British friends -- Ask & tell -- A dignified transfer -- Part III. Homefronts -- To Cherokee, Iowa -- To Menard, Texas -- The parade -- Semper fido and the Sierras -- Operation Mend -- Spirit of America -- The library -- A museum of war -- Nick's home -- The mall of America -- Epilogue: New York City -- After war -- A soldier's war journal, a soldier's mirror test -- Angels.
Keywords: Weston, J. Kael; Weston, J. Kael; United States. -- Dept. of State -- Officials and employees -- Biography; United States. -- Department of State -- Officials and employees -- Biography; Iraq War, 2003-2011.; Afghan War, 2001-2021; Iraq War, 2003-2011 -- Personal narratives, American; Afghan War, 2001-2021 -- Personal narratives, American; Iraq War, 2003-2011.; Afghan War, 2001-; Iraq War, 2003-2011 -- Personal narratives; Afghan War, 2001- -- Personal narratives